Participation of the State, the academic community and society in improving the quality of higher education - Hoyos-Vásquez, Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2013)
To elucidate the role of education in relation to citizenship education as a horizon appears to characterize the sense of quality that is recognized today as ‘relevance’. This quality allows us to understand quality more as a concept related to the society to which belong institutions of higher education, that as something definable by itself. Which in turn requires us to update a characterization of the sense of relations between civil society and State, allowing us to further emphasize the need that the university must be thought mainly in its direct relations with society and only from them redefines its relations with the State. All this will help us more adequately to clarify the meaning of quality of higher education that Colombia needs and in which should commit on the stage of the economy, of culture, of public and educational policy, as agents of change,  the State, academic community and civil society itself .